Copper-catalyzed oxidative cyclization of glycine derivatives toward 2-substituted benzoxazoles. Issue 7 (3rd February 2021) - Liu, Shan; Zhu, Zhi-Qiang; Hu, Zhi-Yu; Tang, Juan; Yuan, En
Abstract : A novel and direct intramolecular cyclization of glycine derivatives involving short peptides to 2-substituted benzoxazoles via copper-catalyzed oxidative C–H/O–H cross-coupling was described. Abstract : A novel and straightforward intramolecular cyclization of glycine derivatives to 2-substituted benzoxazoles through copper-catalyzed oxidative C–H/O–H cross-coupling was described. A variety of glycine derivatives involving short peptides underwent cross-dehydrogenative-coupling readily to afford diverse 2-substituted benzoxazoles. The synthetic method has the advantages of simple operation, broad substrate scope and mild reaction conditions, thus providing an alternative effective approach for benzoxazole construction.